Struktur dan Unsur Kebahasaan Teks Surat Lamaran Pekerjaan Siswa Kelas XII SMA Negeri 3 Painan - Silvia Anggraini; Erizal Gani (Universitas Negeri Padang, 2023)
The purpose of this study is to describe the use of the structure of the job application letter text and describe the use of linguistic elements of the job application letter text for class XII students of SMA Negeri 3 Painan. This type of research is qualitative using descriptive methods. The data of this study is the structure and linguistic elements of the text of the job application letter for class XII students of SMA Negeri 3 Painan. The source of this research data is the text of the job application letter for class XII students of SMA Negeri 3 Painan, which amounts to twenty texts of job application letters. This instrument is a test. Data is analyzed by describing, analyzing, and discussing data based on theory. The theory used is the theory of structure and linguistic elements of the text of a job cover letter. The result of this study is First, the structure of the text of the job application letter written by class XII students of SMA Negeri 3 Painan is still incorrect in writing. Second, the language of the text of the job application letter written by class XII students of SMA Negeri 3 Painan for the use of spelling and effective sentences is appropriate, but for the use of spellings and effective sentences there are still some that are not appropriate.